A robust control technique for stable operation of a DC/AC hybrid microgrid under parameters and loads variations. (May 2020) - Amirkhan, Salman; Radmehr, Masoud; Rezanejad, Mohammad; Khormali, Shahab
Highlights: A passivity theory and sliding mode-based robust control technique for a hybrid dc/ac microgrid. Analytical curves based on various relationships between the state variables errors of converters and the sliding coefficients. Accurate power sharing with parameter and load change to reach microgrid stability. Abstract: In this paper, a robust control technique based on the appropriate definition of sliding mode surfaces is proposed to control a grid-connected hybrid DC/AC microgrid under both parameters and load alterations. The initial loop of proposed control technique is shaped by applying passivity theory to dynamic models of used converters errors. In this stage, the passivity theory enforces the dynamics of the state variables errors to converge zero values with considering the injected impedance and resistance for d-q components currents of inverters and the used DC/DC converters, respectively. Using the error dynamics, proposed sliding mode surfaces are defined to provide more stable movement for the converters-based state variables under parameters variations as the first contribution of this manuscript. To investigate the robustness effects of embedded sliding mode controller, as another contribution, several analytical curves are proposed to find various relationships between the state variables errors of converters and the sliding coefficients obtained through the combination of proposed error dynamics and ultimate control strategy. Both load and hybrid microgrid parameters variations are employed to verify the dynamic and robustness abilities of proposed control technique.